Enhancing soybean tolerance to pre-emergent herbicides via biochar seed coating for eco-safe food systems - Arshad, Muhammad Awais; Abbas, Rana Nadeem; Baloch, Rania; Ahmad, Ali; Zulfiqar, Usman; Haider, Fasih Ullah; El-Beltagi, Hossam S.; Alqahtani, Mashael Daghash; Prasad, P. V. Vara (Frontiers in Plant Science, 2026)
Soybean (Glycine max L.) is highly sensitive to herbicides, which limits the effectiveness of chemical weed control and poses challenges to sustainable production. Biochar, a porous, carbon-rich material with a strong capacity for herbicide adsorption, is commonly applied as a soil amendment; however, its potential use as a seed coating to protect soybean seedlings from herbicide injury remains largely unexplored. To address this gap, a two-year field study (2022-2023) was conducted at the Agronomic Farm, University of Agriculture Faisalabad, to evaluate the effectiveness of biochar-coated soybean seeds in enhancing herbicide tolerance and suppressing weeds. The experiment was laid out in a randomized complete block design with a factorial arrangement, comprising 12 treatments replicated three times. The treatments included biochar-coated seeds and normal seeds, combined with six weed control treatments: s-metolachlor + pendimethalin, s-metolachlor, fluizefop-p-butyl, haloxyfop-p-ethyl, weed-free, and a weedy check. Growth, yield, quality, and weed-related indices were recorded throughout the study. Results revealed that biochar-coated seeds combined with s-metolachlor + pendimethalin significantly reduced weeds dry weight (699.5 and 516.2 kg ha-1), lower susceptibility index (1.5 and 1.2) and higher seed yield (1879.21 and 1933.77 kg ha-1), protein content (34.7% and 35.3%) and oil content (19.3 and 19.8%) in 2022 and 2023, respectively, demonstrating the protective role of biochar against herbicide-induced stress. This treatment also resulted in a 3.12% to 3.95% higher weed control percentage, a 9.93% to 12.55% increase in weed persistence index, and a 3.25% higher weed control efficiency. Moreover, lower weed indices were recorded, with yield losses limited to only 6.66% and 8.93% compared to normal seeds. Overall, these findings confirm that biochar-coated seeds, combined with s-metolachlor and pendimethalin, effectively suppress weeds with minimal crop injury, while also improving protein, oil content, and yield. This highlight biochar-based seed coating as a promising, climate-smart, and environmentally safe strategy for sustainable soybean production, warranting further investigation across diverse agro-ecological conditions.